A Protocol for Argumentation-Based Persuasive Negotiation Dialogues - Morveli-Espinoza, Mariela; Possebom, Ayslan; Tacla, Cesar Augusto (Anais da Brazilian Conference on Intelligent Systems (BRACIS), 2021)
Argumentation-based persuasive negotiation is a form of negotiation dialogue in which agents, with different interests and goals, exchange proposals that are supported by rhetorical arguments such as threats, rewards, or appeals. Besides rhetorical arguments, additional kinds of illocutions may also be exchanged during the dialogue, for instance, agents may ask for explanations, give explanations, or attack (or contradict) previous arguments. This paper presents a formal protocol for argumentation-based persuasive negotiation dialogues in which a proponent agent tries to persuade his opponent to perform a given action and the opponent tries to maintain his position. The protocol is modelled as a dialogue game (i.e. the interactions between the proponent and the opponent are governed by a set of rules) and the outcome of the dialogue is determined by applying an argumentation semantics. We prove the soundness and completeness of our proposal and illustrate the proposed protocol by using an example.